Horacio Bozzano (1ª edición: 2009, 2ª edición: 2012, 3ª edición: 2018). Territorios Posibles. Procesos, lugares y actores. Buenos Aires: Editorial Lumiere, 635 páginas. ISBN 978-987-603-096-0 (2019)
Horacio Bozzano (1ª edición: 2009, 2ª edición: 2012, 3ª edición: 2018). Territorios Posibles. Procesos, lugares y actores. Buenos Aires: Editorial Lumiere, 635 páginas. ISBN 978-987-603-096-0